Structural – electronic properties correlation of CdSe quantum dot solar cell using experimental and theoretical investigations - Saifful Kamaluddin, Muzakir (2015)
Solar cells are in focus for decades due to their capability to convert solar energy into electrical energy. Quantum dots sensitized solar cell (QDSC), in which the photovoltaic (PV) effect occurs at the interface between a quantum dot (QD) conjugated wide band gap metal oxide semiconductor (MOS) and a redox electrolyte, gained much consideration due to their relatively simpler device structure and similarity to dye sensitized solar cell (DSSC), in which dye molecules replace QDs. The QDs are potentially having larger absorption cross-section, tuneable band edges, and atomic-like energy levels. These salient features make QDs capable of delivering more than one electron per single absorbed photon of sufficient energy, a phenomenon known as multi-exciton generation (MEG). The MEG effect makes QDSCs capable of achieving PV conversion efficiency (PCE) as high as 60% theoretically. Despite the remarkable feature of QDs as a light absorber, QDSCs deliver much inferior practical PCE (~8.6 %). Besides, they show inferior PCE compared to DSSCs (~13%). Therefore, this doctoral research aims to establish the structure-property correlation in QDSCs. A combination of experimental results and quantum chemical calculations under the framework of density functional theory (DFT) was employed for this purpose. In this approach, firstly CdSe QDs were synthesized using chemical methods and studied their structure and properties. Secondly realistic cluster models were empirically developed using DFT and experimental results. The structure-property correlation was established by comparing the experimental and theoretical results. The calculated absorption cross-section, band edges, band gaps, and emitting states of QDs with and without surface ligands were compared with that of RuL2(NCS)2.2H2O; L = 2,2’–bipyridyl-4,4’-dicarboxylic acid (N3) dye to correlate the capability of light absorption of QDs or dye molecules on the overall performance of device. This procedure was adopted to (i) understand the fundamental differences of electronic states in the bare QDs and the dye structures and (ii) evaluate electron channelling in QDs-ligand conjugate thus correlating with electron injection efficiency from QDs to MOS. Five parameters were concluded to have distinct effects on the PV properties of QDSCs. They are (i) emitting states of QDs, (ii) ligand usage, (iii) QDs size distribution, (iv) absorption cross-section, and (v) redox potential of electrolyte. The QDs–MOS conjugates were chemically developed and spectroscopically demonstrated efficient electron injection from QDs to MOS. However, such structures raised serious concerns on long term stability under operating conditions. This thesis finally propose future possible methodologies for stable and efficient QDSCs.